SOCIAL MEDIA MARKETING STRATEGY FOR START-UPS AND SMALL AND MEDIUM ENTERPRISES - Khan, Suboohi (Digital Repository of Theses, 2023)
This research aims to understand better how new businesses and entrepreneurs who have difficulty establishing themselves in the business sector may benefit from social media. Traditional marketing has had a great deal of success, but it has also been responsible for the failure of many campaigns due to ineffective strategies. In addition, the proliferation of digital communication technologies like the Internet and other social media platforms has spurred a total rethinking of traditional marketing techniques. It is because of the increased competition that these new technologies provide. These days, businesses place a substantial amount of importance on making the most of the possibilities afforded by digital platforms to get the desired results. Researching which marketing tactics are the most lucrative and valuable for firms and which components of those strategies contribute to their success is now much more desirable due to these changes. Consequently, this study aims to traverse the characteristics that lead to effective social media marketing, particularly emphasising the strategies used by startups and other small to medium-sized businesses. It is the primary research issue that will be addressed in further depth through this article: How can new businesses, especially those that fall into the classification of small to medium in terms of size, make the most of the social media marketing opportunities available to them?